2019
DOI: 10.1039/c9sc01955c
|View full text |Cite
|
Sign up to set email alerts
|

A reactive coordinatively saturated Mo(iii) complex: exploiting the hemi-lability of tris(tert-butoxy)silanolate ligands

Abstract: Hemilabile tris(tert-butoxy)silanolate ligands allow stabilizing a mononuclear octahedral Mo(iii) complex without quenching its reactivity towards small molecules (N2, CO2, N2O).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 54 publications
0
35
1
Order By: Relevance
“…[29,30] Interestingly, the alkyne CÀ C and MÀ C bonds display the same length in both 1a and 1b proving that C 2 Me 2 is naturally a better donor than HC 2 Ph and C 2 Ph 2 . Compared to a recently published five-coordinate Mo(III) C 2 Me 2 adduct with an alkyne CÀ C distance of 1.283 Å, [55] the CÀ C distance in Mo(II) (1b) is slightly longer, while that in Mo(IV) (6b) is a little shorter displaying a nice trend when comparing the different oxidation states of the Mo center.…”
Section: Synthesis Of Oxido Complexescontrasting
confidence: 65%
“…[29,30] Interestingly, the alkyne CÀ C and MÀ C bonds display the same length in both 1a and 1b proving that C 2 Me 2 is naturally a better donor than HC 2 Ph and C 2 Ph 2 . Compared to a recently published five-coordinate Mo(III) C 2 Me 2 adduct with an alkyne CÀ C distance of 1.283 Å, [55] the CÀ C distance in Mo(II) (1b) is slightly longer, while that in Mo(IV) (6b) is a little shorter displaying a nice trend when comparing the different oxidation states of the Mo center.…”
Section: Synthesis Of Oxido Complexescontrasting
confidence: 65%
“…In addition, the MoL 3 fragment is isolobal to a nitrogen atom by its three unpaired electrons populating the mainly dnormalz2 , d xz and d yz molecular orbitals, providing a significant thermodynamic stability to the corresponding Mo nitrides. A second Mo III complex displaying similar reactivity towards dinitrogen was reported more than 20 years later [30] . When the octahedral complex [Mo III (OSi(O t Bu) 3 ) 3 ] ( 3 ) was exposed to dinitrogen, the corresponding mononuclear nitride complex ( 4 ) could be formed (Scheme 5 b).…”
Section: Dissociative Mechanismmentioning
confidence: 55%
“…27,28 After this milestone work, other research groups reported the formation of similar nitride complexes via direct cleavage of the bridging dinitrogen on dinitrogen-bridged dinuclear complexes. [29][30][31][32][33][34][35][36][37][38][39][40][41][42] Interestingly, Cummins and co-workers reported the formation of nitriles from reactions of nitride complexes with acid chlorides. [43][44][45] This research group successfully achieved a pseudo catalytic cycle to convert dinitrogen into nitriles with a stoichiometric amount of transition metal complexes.…”
Section: Introductionmentioning
confidence: 99%